2021
DOI: 10.21203/rs.3.rs-648539/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analyzing the Contribution of Crop Diversification in Improving Household Nutrition Security Among Wheat-dominated Rural Households in Sinana District, Bale Zone, Oromia Regional State, Ethiopia.

Abstract: The long-term impact of malnutrition on people’s lives, most notably in health, education, and productivity, highly affects the human capital. Agriculture directly contributes to nutrition security by enabling farm households to access micronutrient food by using their farm income. This study was intended to assess effect of crop diversification on household nutrition security and explores determinants of under-five child malnutrition among rural farm households of Sinana Woreda, Oromia regional state. Multi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Consistent with prior studies, we identified a strong positive correlation between CDI and DDS at the district level (Dabo et al, 2013;Singh et al, 2020;Dereje et al, 2021;Derso et al, 2021;Mengistu et al, 2021;Azupogo et al, 2023). There is empirical support for a beneficial link between crop diversity and dietary diversity, which two distinct mechanisms may mediate: (1) by providing a farmer's household with a variety of food groups to consume and ( 2) by providing a variety of crops that can be sold to the market to generate income that is used to purchase a wider variety of foods from markets (Achterbosch et al, 2014;Hill and Vigneri, 2014;Ntakyo and van den Berg, 2019;Baker et al, 2020;Soukand et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with prior studies, we identified a strong positive correlation between CDI and DDS at the district level (Dabo et al, 2013;Singh et al, 2020;Dereje et al, 2021;Derso et al, 2021;Mengistu et al, 2021;Azupogo et al, 2023). There is empirical support for a beneficial link between crop diversity and dietary diversity, which two distinct mechanisms may mediate: (1) by providing a farmer's household with a variety of food groups to consume and ( 2) by providing a variety of crops that can be sold to the market to generate income that is used to purchase a wider variety of foods from markets (Achterbosch et al, 2014;Hill and Vigneri, 2014;Ntakyo and van den Berg, 2019;Baker et al, 2020;Soukand et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with prior studies, we identified a strong positive correlation between CDI and DDS at the district level (Dabo et al, 2013;Singh et al, 2020;Dereje et al, 2021;Derso et al, 2021;Mengistu et al, 2021;Azupogo et al, 2023). There is empirical support for a beneficial link between crop diversity and dietary diversity, which two distinct mechanisms may mediate: (1) by providing a farmer's household with a variety of food groups to consume and (2) by providing a variety of crops that can be sold to the market to generate income that is used to purchase a wider variety of foods from markets (Achterbosch et al, 2014;Hill and Vigneri, 2014;Ntakyo and van den Berg, 2019;Baker et al, 2020;Soukand et al, 2020).…”
Section: Discussionsupporting
confidence: 90%